DDDR-01. AZD9574 IS A NOVEL, BRAIN PENETRANT PARP-1 SELECTIVE INHIBITOR WITH ACTIVITY IN AN INTRACRANIAL XENOGRAFT MODEL OF TRIPLE NEGATIVE BREAST CARCINOMA WITH HOMOLOGOUS RECOMBINATION REPAIR DEFICIENCY. (14th November 2022) - Jamal, Kunzah; Staniszewska, Anna; Gordon, Jacob; Pilger, Domenic; Illuzzi, Giuditta; Wilson, Joanne; Smith, Aaron; Gosselin, Eric; McWilliams, Lisa; Wen, Shenghua; McGrath, Frank; Dowdell, Gregory; et al.
Abstract: The Poly (ADP-ribose) polymerase (PARP) family has numerous essential functions in cellular processes such as transcription, chromatin remodelling, DNA damage response and repair as well as apoptosis. PARP inhibition blocks base excision repair and results in conversion of SSBs to DNA double-strand break (DSBs), the most deleterious form of DNA damage. DSBs can be repaired by homologous recombination repair (HRR) or non-homologous end joining (NHEJ). The physiological importance of HRR is underscored by the observation of genomic instability in HRR-deficient (HRD+) cells and, importantly, the association of cancer predisposition and developmental defects with mutations in HRR genes. PARP1 and PARP2 are required for SSB repair, while PARP1 is also involved in the repair of DNA double-strand breaks (DSBs) and replication fork damage. AZD9574 is a novel brain penetrant PARP1 inhibitor that acts by selectively inhibiting and trapping PARP1 at the sites of SSBs. While AZD9574 inhibited PARP1 enzymatic activity in all tested cell lines irrespective of the HRR status (IC50 range between 0.3 – 2 nM), colony formation assay in isogenic cell lines pairs confirmed higher potency and selectivity towards HRD+ models. In vivo, AZD9574 demonstrated dose-dependent efficacy in a BRCA1 mutant MDA-MB-436 subcutaneous xenograft model. Anti-tumour effects of AZD9574 were manifested by significant growth regressions that were durable after treatment withdrawal. An intracranial xenograft model of breast cancer brain metastases was developed to assess the efficacy of AZD9574 in the context of blood-brain barrier penetrance. Treatment of animals with established intracranial lesions showed sustained tumour growth suppression resulting in a significantly extended survival of tumour-bearing mice. Collectively, we believe that our data support the development of AZD9574 as a potential therapy for patients with HRD + breast cancer whose disease has spread to the brain.This abstract was previously presented at AACR 2022 (Hamerlik et al, AACR 2022, Abs #3880)